Effect of Age-Related Cartilage Turnover on Serum C-Telopeptide of Collagen Type II and Osteocalcin Levels in Growing Rabbits with and without Surgically Induced Osteoarthritis. (5th March 2014) - Huang, Chung-Cheng; Lee, Chen-Chang; Wang, Ching-Jen; Wang, Feng-Sheng; Huang, Hsuan-Ying; Ng, Shu-Hang; Tseng, Chia-Yi; Ko, Sheung-Fat
Abstract : This study aims to determine the effect of age-related cartilage turnover on the serum C-telopeptide of type II collagen (CTX-II) and osteocalcin (OC) levels in growing rabbits with and without surgically induced osteoarthritis. Twenty-four New Zealand male 3-month-old rabbits were randomized into three operated groups ( n = 6 per group, with surgically induced osteroarthritis in the right knee; after blood sampling, the knees were harvested following euthanization at 2, 3, and 6 months after surgery) and a control group ( n = 6, blood samples were obtained monthly between 3 and 15 months). Histomorphologically, the medial femoral condyles, particularly the central parts, harbored the most severe osteoarthritic changes among the operated rabbits. The serum levels of CTX-II and OC decreased in the controls from 3 to 11 months and then remained stable. No significant differences in the serum CTX-II and OC levels between the osteoarthritic rabbits and controls were observed. The osteoarthritic-to-normal ratios (ONRs, the ratios of serum CTX-II or OC levels in osteoarthritic rabbits to those of the controls at same ages) enabled an overall assessment of osteoarthritis and age-related cartilage turnover. Elevated CTX-II ONRs were observed in rabbits with mild to advanced osteoarthritis. However, the OC ONRs were unhelpful in assessing osteoarthritic growing rabbits.